Comparison of the efficacy of Inula viscose leaves extract with metronidazole against Giardia lamblia cysts: an experimental study - ديوب, أمل; سلامة, ريم; الحكيم, السموءل (Latakia University Journal -Biological Sciences Series, 2022)
This study aimed to determine the effectiveness of Inula viscosa (L.) in comparison with metronidazole to eliminate the cysts of Giardia lamblia, as it is one of the most common plants in our local environment. Infection due to the protozoa giardia is one of the most common parasitic infections in the world. Millions of people across the world acquire this infection each year. The most common clinical symptoms of giardiasis include abdominal pain, bloating diarrhea, indigestion, epigastric pain, nausea, vomiting and fatty foul-smelling stools. Using known Drugs to treat giardiasis causes certain side effects, such as unpleasant taste in the mouth, gastrointestinal discomfort, nausea, headache and leukopenia. Considering the widespread nature of giardiasis infection, it is essential to identify anti-parasitic herbal drugs to eliminate cystic and trophozoite types of this disease. The results of the laboratory study showed that the ethanolic extract of Inula viscose leaves is highly effective in eliminating giardia cysts. The percentage of dead cysts was rated 58%, for 3 hours of incubation, while this percentage of metronidazole was 38% Thus, Inula viscose has nearly twice the efficacy of the selective drug metronidazole at tested concentration.